2021
DOI: 10.1007/s00702-021-02390-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of the 5-HTTLPR polymorphism and the response to different stressors in healthy males

Abstract: The experience of stress is related to individual wellbeing and vulnerability to psychopathology. Therefore, understanding the determinants of individual differences in stress reactivity is of great concern from a clinical perspective. The functional promotor polymorphism of the serotonin transporter gene (5-HTTLPR/rs25531) is such a factor, which has been linked to the acute stress response as well as the adverse effect of life stressors. In the present study, we compared the impact of two different stress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The BSKE ( Befindlichkeitsskalierung durch Kategorien und Eigenschaftswörter , Janke, 1994) scales are a short version of the more extensive “ Eigenschaftswörterliste ” (EWL 107 , a scale developed to assess the current emotional state across positive and negative dimensions. This reduced scale consists of 15 items (emotions/states) relevant for anxiety that have been previously used to assess stress reactivity 47 , 48 , 108 and comparable to the PANAS or state anxiety questionnaire that are also used in stress research 109 , 110 assess different emotions and feelings that might be affected by stress such as agitation, anxiety, anger, or sensitivity. Participants were asked to rate their current state/feeling (“I feel …”) on 6-point scale ranging from 1 (“not at all/gar nicht”) to 6 (“very strongly/sehr stark”).…”
Section: Methodsmentioning
confidence: 99%
“…The BSKE ( Befindlichkeitsskalierung durch Kategorien und Eigenschaftswörter , Janke, 1994) scales are a short version of the more extensive “ Eigenschaftswörterliste ” (EWL 107 , a scale developed to assess the current emotional state across positive and negative dimensions. This reduced scale consists of 15 items (emotions/states) relevant for anxiety that have been previously used to assess stress reactivity 47 , 48 , 108 and comparable to the PANAS or state anxiety questionnaire that are also used in stress research 109 , 110 assess different emotions and feelings that might be affected by stress such as agitation, anxiety, anger, or sensitivity. Participants were asked to rate their current state/feeling (“I feel …”) on 6-point scale ranging from 1 (“not at all/gar nicht”) to 6 (“very strongly/sehr stark”).…”
Section: Methodsmentioning
confidence: 99%
“…The S allele correlates with anxiety disorders and some anxiety-related traits according to several studies and meta-analyses [25][26][27]. It has been found that individuals carrying lowerexpression variants of rs774676466 are more susceptible to various types of stress [28]. Nonetheless, there are still debates regarding the clinical significance of this promoter variant [29].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Sattler and colleagues show evidence that contextual information may only matter to a certain extent, as in their study (Sattler et al 2021), the biological response to a gay-specific social stressor was equally pronounced as the one to a general social stressor in gay men. Genetic information is probably the most widely researched dispositional factor; Kuhn et al show in their paper (Kuhn et al 2021) that the low expression variant of the serotonin transporter gene serves as a risk factor for increased stress reactivity, thus clearly indicating the important role of dispositional factors in stress processing. An interesting factor combining both aspects of dispositional and contextual information is maternal care; Bentele et al (2021) in their study are able to show that there was an effect of maternal care on the amylase stress response, while no such effect was observed for cortisol.…”
mentioning
confidence: 99%